Young Adults' Responses to Infant Names. (1st September 2013) - Powell, Darcey N; Karraker, Katherine
Abstract : Many parents in the United States devote a great deal of attention to selecting their children's names. To better understand this process, 532 potential parents in the United States rated their liking and perceptions of infant names. Liking was related to characteristics of the names (such as popularity, defined as how frequently the names had been previously selected by parents) and to characteristics of the raters (such as their personality traits and gender). Ratings of the physical and behavioral traits of infants depicted through both a name and a photograph were related more strongly to ratings of the photograph alone than the name alone. These results suggest that parent preferences for certain names may account for changes in name popularity over time, and also suggest that the influence of names on adults' perceptions of infants may be superseded by the influence of the infants' physical appearance.